2000
DOI: 10.1126/science.288.5472.1828
|View full text |Cite
|
Sign up to set email alerts
|

Economic Incentives for Rain Forest Conservation Across Scales

Abstract: Globally, tropical deforestation releases 20 to 30% of anthropogenic greenhouse gases. Conserving forests could reduce emissions, but the cost-effectiveness of this mechanism for mitigation depends on the associated opportunity costs. We estimated these costs from local, national, and global perspectives using a case study from Madagascar. Conservation generated significant benefits over logging and agriculture locally and globally. Nationally, however, financial benefits from industrial logging were larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(156 citation statements)
references
References 17 publications
2
152
0
2
Order By: Relevance
“…As previously explained, in Madagascar conservation restrictions usually entail a decrease in agricultural production because farmers can no longer clear primary forest to manage soil fertility. Previous research in Madagascar studying the costs of conservation for local populations has not assessed the impacts on livelihoods; it has used either a contingent valuation approach, such as the "willingness-to-accept" methodology (Kramer et al 1 995,Shyamsundar and Kramer 1 996,Desbureaux and Brimont 201 5), or the opportunity costs method, in which the authors assess the potential income derived from practising agriculture on newly deforested land (Kremen et al 2000, Ferraro 2002). For the purpose of this article, we chose to estimate the loss of household income arising from the implementation of the Beampingaratsy REDD+ project, i.e., restrictions on the use of natural resources established by VOI management plans, as a way of estimating the de facto real conservation cost for local populations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously explained, in Madagascar conservation restrictions usually entail a decrease in agricultural production because farmers can no longer clear primary forest to manage soil fertility. Previous research in Madagascar studying the costs of conservation for local populations has not assessed the impacts on livelihoods; it has used either a contingent valuation approach, such as the "willingness-to-accept" methodology (Kramer et al 1 995,Shyamsundar and Kramer 1 996,Desbureaux and Brimont 201 5), or the opportunity costs method, in which the authors assess the potential income derived from practising agriculture on newly deforested land (Kremen et al 2000, Ferraro 2002). For the purpose of this article, we chose to estimate the loss of household income arising from the implementation of the Beampingaratsy REDD+ project, i.e., restrictions on the use of natural resources established by VOI management plans, as a way of estimating the de facto real conservation cost for local populations.…”
Section: Methodsmentioning
confidence: 99%
“…The payments for environmental services (PES) literature usually distinguishes between three types of costs: (i) opportunity costs, i.e., households' forgone revenues from the protection of ecosystems, (ii) transaction costs, which cover the start-up and running costs incurred by the implementation and functioning of PES, and (iii) the actual payments ( Kremen et al 2000, Ferraro 2002, and the transaction costs of direct incentive schemes in tropical countries (Angelsen 2008, Börner and Wunder 2008, Grieg-Gran 2008). …”
Section: Payments For Environmental Services (Pes)mentioning
confidence: 99%
“…According to Kremen et al [35], conservation benefits are global, but cost is mainly incurred by local communities who must forgo exploitation rights and restriction from forest and forest resources for the sake of conservation, despite high cultural and livelihoods implications. Past PES programmes showed mixed results in benefits to local communities [36].…”
Section: Local Engagement and Expectationsmentioning
confidence: 99%
“…And it is varying due to the fact that it encompassed by a fluctuating external environment, which implies that changes of hydrological ecosystem services could be for or against human well-being. However, Kremen et al (2000) and McConnell (2002) proposed that the overall impacts of ecosystem services on human well-being cannot be determined by the research in one region or modeling through using shortterm data. Identically, Daw et al (2011) concluded that people benefited from ecosystem services constrained by the family size, education level, poverty, vulnerability, and social relations.…”
Section: Effects Of Regional Hydrological Ecosystem Services On Humanmentioning
confidence: 99%